Map & Bookshop, l’archivio cartografico della Regione Emilia - Morenzetti, Ugo (GEOmedia, 2009)
Map & Bookshop, the cartographic archive of Emilia-Romagna Region The cartographic archive of Emilia-Romagna Region is almost like a real bookshop which also stocks cartographic material and publications on various issues. Founded in late 70's, the archive constantly enhanced its capabilities, offering a wider variety of products and introducing, since 2001, an e-commerce service